(3fjd GdEHJgGL HJWQjR GdOjHGLs - (3CHi GdYHGS CMeO Hf YeQ Hf eMeO HGHG GdJcQhQi GdJfHci GdeGdcjs; (3Ydj Hf eMeO Hf aQMhf GdbjSj GdbQWHj GdCfOdSj GdeGdcj , CHh GdMSf,J (B601 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdefaQO HGdHbGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B330 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B225s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B176 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B329 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs